Enhancing properties of Fe-Cr-alumina composites prepared by powder metallurgy / Saidatulakmar Shamsuddin... [et al.] - Shamsuddin, Saidatulakmar; Jamaludin, Shamsul Baharin; Hussain, Zuhailawati; Ahmad, Zainal Arifin (Universiti Teknologi MARA, Perlis, 2014)
Fe-based matrix composites have shown the potential for use as advanced materials for technological applications. In this study metal matrix composites (MMCs) of Fe-Cr –alumina were fabricated by powder metallurgy (PM). The effect of alumina content on the physical and mechanical properties of the composites was investigated. Scanning Electron Microscope (SEM) showed a homogeneous distribution of alumina in the matrix. Energy Dispersive X-ray (EDX) displayed the presence of Fe, Cr and alumina in the composites. Optimum condition of the composites was examined by evaluation of the parameters such as density, porosity, shrinkage, hardness, wear resistance and compressive strength. Results showed that addition of alumina greater than 5 wt. % decreased the density but increased porosity. Hardness and wear resistance of the composites increased with increasing alumina content to 20 wt. %. However, the compressive strength showed optimal value at 5 wt. % alumina.